Implementasi Algoritma RC4A Dalam Pengamanan Citra Digital - Yanti Nur Iman Giawa (Journal of Computing and Informatics Research, 2022)
Digital images that are private and confidential are very vulnerable to wiretapping by irresponsible parties, especially if the images are distributed via the internet. The act of theft and abuse of secret images of course can harm the image owner. One of the techniques to reduce the above problems is by using cryptographic techniques. Cryptographic techniques can secure images by means of digital image encryption by implementing the RC4A algorithm then using the initial keyword as input in the process carried out to generate new, more random keywords, based on the Key Schedule Algorithm. (KSA) and pseudo random generation algorithm (PRGA). To determine the comparison between the original image (PlainImage) and the original image (CipherImage), processing was carried out with MeanSquareError (MSE) and PeakSiqnalToNoiseRation (PSNR). The results of this study were digital images encrypted with the RC4A algorithm in terms of time differences and image results after encryption where the time used to encrypt is shorter than the description and the image results before encryption are not the same after encryption.